Intervention with Victims of Forced Marriage. Issue 3 (4th May 2022) - Torres, Núria; Villacampa, Carolina
Abstract: The article presents results of a qualitative research aimed at analyzing how professionals work to support and protect victims of forced marriage in Spain. The study is based on the information gathered from professionals involved in criminal justice and in victim support with whom in-depth interviews were conducted. Given the increasingly common opinion favorable to address forced marriage from a victim-centred and intersectional perspective, away from those that focus on criminalization and cultural "otherness', the research presents the landscape of provisions aimed at preventing and supporting victims of forced marriage in this country. Additionally, the article gives an overview on how professionals adjust scarce resources and unclear paths to earlier detect and to better support victims of this complex phenomenon.